(untitled) (Revista Contexto & Saúde, 2026)
The emerging crisis of the COVID-19 pandemic brought several challenges related to mental health. As a response to this sudden situation, the general population may have presented psychological symptoms, including the use of psychoactive substances. This study aimed to identify factors associated with the initiation of alcohol, psychopharmaceuticals, and/or other psychoactive substance use during the pandemic. This was a cross-sectional observational study conducted between April and September 2021 with 2,469 participants (students, professors, and staff) from four federal universities located in the Central-West region of Brazil. Logistic regression analysis was performed to estimate odds ratios. Overall, approximately one-quarter of participants reported initiating substance use during the COVID-19 pandemic. Psychopharmaceuticals were the most frequently reported substances among both students and professors/staff, followed by alcohol. Among students, the initiation of alcohol use was associated with living with friends/roommates, belonging to a risk group for severe COVID-19 illness, and having experienced domestic violence during social distancing measures. Different individual and social factors were associated with the initiation of substance use during the pandemic, with younger age and student status being related to the onset of illicit substance use.